2014
DOI: 10.1144/jgs2013-131
|View full text |Cite
|
Sign up to set email alerts
|

Ganderia–Laurentia collision in the Caledonides of Great Britain and Ireland

Abstract: Analytical procedures and results: U-Pb detrital zircon geochronologyDetrital zircons were analysed at the University of Alberta Radiogenic Isotope facility. Samples were crushed and zircons were separated and concentrated by standard techniques using a Wilfley table, heavy liquids and magnetic separator. The grains were ablated using a New Wave Research UP213 Nd:YAG with aperture imaging system. The wavelength was 213 nm, with a fluence of 3 Jcm -2 , a 4 Hz pulse rate and a spot size of 40 µm. Ablated ions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 113 publications
7
68
0
Order By: Relevance
“…However, provenance evidence from the Northern Belt of the Southern Uplands makes this unlikely at the terrane boundary. The derived (in sediment mass flows) shelly faunas in the Kirkcolm Formation have relatively locally, in situ correlatives in the Midland Valley Terrane, albeit in Ireland, whilst detrital mineral grains and zircon dating make a Dalradian provenance likely for all of the sandstones of the Southern Uplands Terrane (Clarkson et al 1992;Hutchinson & Oliver 1998;Mange et al 2005;Waldron et al 2008Waldron et al , 2014 Ireland. There, a high-resolution, airborne conductivity survey proved spectacularly successful in delineating the thin zones of carbonaceous mudstone in the DownLongford extension of the Southern Uplands Terrane, including concealed inliers with no apparent surface exposure (Beamish et al 2010).…”
Section: Concluding Discussion: Consensus and Outstanding Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, provenance evidence from the Northern Belt of the Southern Uplands makes this unlikely at the terrane boundary. The derived (in sediment mass flows) shelly faunas in the Kirkcolm Formation have relatively locally, in situ correlatives in the Midland Valley Terrane, albeit in Ireland, whilst detrital mineral grains and zircon dating make a Dalradian provenance likely for all of the sandstones of the Southern Uplands Terrane (Clarkson et al 1992;Hutchinson & Oliver 1998;Mange et al 2005;Waldron et al 2008Waldron et al , 2014 Ireland. There, a high-resolution, airborne conductivity survey proved spectacularly successful in delineating the thin zones of carbonaceous mudstone in the DownLongford extension of the Southern Uplands Terrane, including concealed inliers with no apparent surface exposure (Beamish et al 2010).…”
Section: Concluding Discussion: Consensus and Outstanding Issuesmentioning
confidence: 99%
“…The picture is further complicated by a likely Dalradian provenance for most of the detrital zircons in Southern Uplands sandstones (e.g. Waldron et al 2008Waldron et al , 2014 Midland Valley conglomerates. These were derived from the south but from a provenance that is not represented within the currently exposed Southern Uplands Terrane, a circumstance established by a wide range of evidence and discussed by, amongst others, Bluck (1983Bluck ( , 1984, Syba (1989), Stone & Evans (2001) and Phillips et al (2004).…”
Section: Concluding Discussion: Consensus and Outstanding Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…(Kimbell & Stone 1995;Phillips et al 2003). See subsequent discussion by Waldron et al (2008Waldron et al ( , 2014 (Allen & Jackson 1985;Pratt et al 1995;Howells & Smith 1997). The age of the Rosslare gneisses is not known, but they have a complex metamorphic history which predates intrusions dated at 650 Ma (Winchester & Max 1982 Bott et al (1972) suggested magnetic Scourian gneiss at shallow depth but this was not supported by a seismic refraction experiment (Hall & Al-Haddad 1979).…”
Section: G Galloway Anomalymentioning
confidence: 99%